Effect of a novel clay/silica nanocomposite on water-based drilling fluids: Improvements in rheological and filtration properties - Cheraghian, G.; Wu, Q.; Mostofi, Masood; Li, M.; Afrand, M. (Elsevier BV, 2018)
Drilling fluid is one of the most important components of drilling operation in oil and gas, mining and geothermal industries. Nanotechnology can be used to develop drilling fluid additives that can improve the drilling fluid properties. In this work, the feasibility of using two types of nanoparticle additives in water-based drilling fluid has been investigated. Clay/SiO2 nanocomposite was synthesized (by effective hydrothermal method) and successfully characterised. A series of experiments are performed to evaluate the effect of SiO2 and clay nanoparticles on the rheological and filtration properties of water-base drilling fluids. The experiments are conducted at different concentrations of Clay/SiO2 and SiO2 nanoparticles, and also at a range of temperatures. The results showed that the addition of clay and SiO2 nanoparticles improved the rheological and fluid loss properties. It was also noticed that the nanoparticles provide thermal stability to the drilling fluid. The experimental results suggest that the Clay/SiO2 nanoparticles have a more significant impact on the rheological and fluid loss properties of the drilling fluid comparing to SiO2 nanoparticles, particularly at higher temperatures.